The Role of Management In Improving The Nutritional Status of Children Under Five in Pekalongan City - Rasnasuri, Dita; Kartini, Apoina; Suyatno, Suyatno (Eduvest - Journal of Universal Studies, 2025)
Malnutrition among children under five remains a significant public health issue in Pekalongan City, affecting their growth, development, and long-term quality of life. In response, the local government has implemented a Supplementary Feeding Program (PMT) using locally sourced, high-nutrient food ingredients that are affordable and accessible. This study aims to analyze the implementation of local food-based PMT and its impact on improving the nutritional status of malnourished children under five. Employing a mixed methods approach, the study combined quantitative research using a case control design with qualitative data from in-depth interviews. A total of 280 malnourished children were selected through purposive sampling. Key variables measured included nutritional status (based on weight-for-age) and the type and frequency of PMT provided. Data were collected via anthropometric assessments and direct observation, and analyzed using the Wilcoxon test. The findings revealed a statistically significant improvement in the nutritional status of the children following a 30-day local food-based PMT intervention (p < 0.05). The PMT menus—featuring ingredients such as tempeh, eggs, sweet potatoes, and local vegetables—were shown to meet daily energy and macronutrient requirements. The study concludes that local food-based PMT is an effective, sustainable strategy to address childhood malnutrition and can serve as a model for community-based nutrition interventions.